Pengembangan Komik Digital Berbasis Google Sites “KOLEGA” tentang Saling Menghargai pada Pembelajaran PAI Kelas 5 SD - Maulida, Kamila Wulan; Nurmutmainah, Siti Khaliza; Aeni, Ani Nur (Program Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2025)
This research aims to develop Google Sites-based e-Comics that focuses on Islamic Religious Education (PAI) material on mutual respect for grade 5 elementary school students. The method used is Design and Development (D&D), which includes problem identification, design, development, product testing, and evaluation of results. This research was conducted at SDN Sukasirna 1 involving 24 students as participants. The e-Comic development process involves several stages, namely needs analysis, formulation of learning objectives, media design, e-Comic production, validation by experts, and product trials in the field. The results showed that the e-Comic “KOLEGA” succeeded in increasing students' understanding of the importance of mutual respect in everyday life. In addition, the results of expert validation and assessment from students and teachers show that this e-Comic is suitable for use as an interesting and effective learning media. The use of Google Sites-based e-Comics media is proven to facilitate the delivery of material and increase students' motivation and enthusiasm for learning. Overall, this research contributes to the development of technology-based learning media that can support the learning process of PAI in elementary schools.